Druggability of the guanosine/adenosine/cytidine nucleoside hydrolase from Trichomonas vaginalis - Alam, Rayyan (Chem Biol Drug Des, 2018)
Trichomonas vaginalis infects approximately 300 million people worldwide annually. Infected individuals have a higher susceptibility to more serious conditions such as cervical and prostate cancer. The parasite has developed increasing resistance to current drug therapies, with an estimated 5% of clinical cases resulting from resistant strains, creating the need for new therapeutic strategies with novel mechanisms of action. Nucleoside salvage pathway enzymes represent novel drug targets since these pathways are essential for the parasite’s survival. The guanosine/adenosine/cytidine nucleoside hydrolase (GACNH) may be particularly important as its expression is upregulated under glucose-limiting conditions mimicking those that occur during infection establishment. GACNH was screened against the NIH Clinical Collection to explore its druggability. Seven compounds were identified with IC(50) values less than 20 μM. Extensive overlap was found between inhibitors of GACNH and the adenosine/guanosine nucleoside hydrolase (AGNH), but no overlap was found with inhibitors of the uridine nucleoside hydrolase (UNH). The guanosine analog ribavirin was the only compound found to be specific for GACNH. Compounds that inhibit both AGNH and GACNH purine salvage pathway enzymes may prove critical given the role that GACNH appears to play in the early stages of infection.